Effect of aerobic packaging on storage quality of functional restructured spent hen meat slices at refrigeration temperature. Issue 3 (8th May 2017) - Gupta, Swati; Sharma, B.D.
Abstract : Purpose: The aim of this work was to study the effect of aerobic packaging on storage quality of functional restructured spent hen meat slices (FRSHMS) at refrigerated temperature (4 ± 1°C). Design/methodology/approach: FRSHMS were prepared by replacing the lean meat with different binders and extenders in pre-standardized restructured spent hen meat slices formulation. The slices of control and FRSHMS were aerobically packaged in LDPE and analyzed for physicochemical, microbiological and sensory quality. Findings: The pH of FRSHMS was significantly higher ( p = 0.03) than control on 0 and 7th day. Thiobarbituric acid (TBA) values of both control and FRSHMS increased significantly on 21st day of storage as compared to 0 day. TBA value of FRSHMS was significantly lower ( p = 0.04) as compared to that of control on 21st day. Psychrophils were detected on 14th day of storage and thereafter increased significantly ( p = 0.00) in both control and FRSHMS. Coliforms were detected only on 21st day of storage in both control and FRSHMS. The sensory attributes of control, and FRSHMS were affected from 14th day onwards, but the products remained quite acceptable with sensory rating between good to very good up to 21 days during refrigerated storage. Research limitations/implications: The trials can be further carried in modified atmospheric packaging to evaluate storage stability of developed restructured spent hen meat slices. Originality/value: The paper has demonstrated that the FRSHMS could be stored safely in aerobic packaging for 21 days at refrigeration temperature.